Prevalence and risk factors of seafood-borne Vibrio vulnificus in Asia: a systematic review with meta-analysis and meta-regression - Tanveer, Maryum; Ntakiyisumba, Eurade; Won, Gayeon (Frontiers in Microbiology, 2024)
Vibrio vulnificus is a free-living marine bacterium associated with the contamination of fish and shellfish—the most consumed seafood in Asia. Owing to its potentially lethal clinical consequences, the consumption of seafood contaminated with V. vulnificus has become a growing public health concern. This systematic review with meta-analysis and meta-regression aimed to integrate data on the prevalence of seafood-borne V. vulnificus specifically in Asia and assess the potential risk factors that can influence the outcomes. A comprehensive literature search of four electronic databases yielded 279 relevant studies, among which 38 fulfilled the inclusion criteria. These selected studies were subjected to risk-of-bias assessment and data extraction by three independent researchers. A meta-analysis of the eligible studies estimated the overall prevalence of seafood-borne V. vulnificus in Asia to be 10.47% [95% confidence interval (CI): 6.8–15.8%], with bivalve shellfish, such as oysters, mussels, clams, and cockles being the most contaminated seafood. The highest prevalence was reported in Japan, where 47.6% of the seafood samples tested positive for V. vulnificus. The subgroup and meta-regression analyses identified three potential covariates—detection method, publication year, and country—associated with between-study heterogeneity. Furthermore, data visualization displayed the variations in V. vulnificus prevalence across the studies, associated with differences in sample type, sample size, and sampling stage. This study provides valuable insights into the prevalence of V. vulnificus in fish and shellfish across the entire Asian continent and highlights the potential factors that cause variation in the prevalence rates among the studies. These findings underscore the importance of enhancing hygiene measures throughout the seafood supply chain to mitigate V. vulnificus infection risks and ensure the safety of consumers.